Local dielectric function of hBN-encapsulated WS2 flakes grown by chemical vapor deposition. (12th July 2023) - Ferrera, Marzia; Sharma, Apoorva; Milekhin, Ilya; Pan, Yang; Convertino, Domenica; Pace, Simona; Orlandini, Giorgio; Peci, Ermes; Ramò, Lorenzo; Magnozzi, Michele; Coletti, Camilla; Salvan, Georgeta; et al.
Abstract: Hexagonal boron nitride (hBN), sometimes referred to as white graphene, receives growing interest in the scientific community, especially when combined into van der Waals (vdW) homo- and heterostacks, in which novel and interesting phenomena may arise. hBN is also commonly used in combination with two-dimensional (2D) semiconducting transition metal dichalcogenides (TMDCs). The realization of hBN-encapsulated TMDC homo- and heterostacks can indeed offer opportunities to investigate and compare TMDC excitonic properties in various stacking configurations. In this work, we investigate the optical response at the micrometric scale of mono- and homo-bilayer WS2 grown by chemical vapor deposition and encapsulated between two single layers of hBN. Imaging spectroscopic ellipsometry is exploited to extract the local dielectric functions across one single WS2 flake and detect the evolution of excitonic spectral features from monolayer to bilayer regions. Exciton energies undergo a redshift by passing from hBN-encapsulated single layer to homo-bilayer WS2, as also confirmed by photoluminescence spectra. Our results can provide a reference for the study of the dielectric properties of more complex systems where hBN is combined with other 2D vdW materials into heterostructures and are stimulating towards the investigation of the optical response of other technologically-relevant heterostacks.